2016
DOI: 10.18869/acadpub.jafm.68.225.24606
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the Aerodynamic Performance of NLF-0414 Iced-Airfoil

Abstract: Icing phenomenon on a natural laminar flow airfoil (NLF-0414) has been experimentally investigated. Double horn glaze ice geometry which was acquired during a 15 minutes spray time at−2.23℃ with liquid water content and a median volumetric diameter of 1.0 g/m 3 and 20 μm, has been extracted from database of NASA Lewis Research Center. Pressure distribution over airfoil surfacewas evaluated at angles of attack between -2 to 6 degreesfor both iced and clean airfoils. Aerodynamics performance degradation of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…They found that the coefficient of lift decreased and the coefficient of drag increased once the ice had formed. Ebrahimi et al (2016) conducted experimental studies on an NLF-0414 profile under well-defined icing conditions to study the degradation of its aerodynamic performance. It was determined that the accumulation of double-horn ice strongly altered the aerodynamic characteristics of the profiles and that the size of the separation bubble on the top side increased with the angle of attack, in contrast to the one located at the bottom surface.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the coefficient of lift decreased and the coefficient of drag increased once the ice had formed. Ebrahimi et al (2016) conducted experimental studies on an NLF-0414 profile under well-defined icing conditions to study the degradation of its aerodynamic performance. It was determined that the accumulation of double-horn ice strongly altered the aerodynamic characteristics of the profiles and that the size of the separation bubble on the top side increased with the angle of attack, in contrast to the one located at the bottom surface.…”
Section: Introductionmentioning
confidence: 99%
“…Jin et al [20] experimentally studied the e ects of a simulated single-horn glaze ice accreted on rotor blades on the vortex structures in the wake of a HAWT utilizing the stereoscopic particle image velocimetry (Stereo-PIV) technique. More recently, Ebrahimi et al [21] experimentally investigated the upper and lower separation bubbles over a Natural Laminar Flow (NLF-0414) airfoil with double horn glaze ice geometry. In addition, Manshadi and Esfeh [22] studied the characteristics of the unsteady separation bubbles on a NACA 0015 airfoil with simulated two-dimensional leading-edge glaze ice accretions.…”
Section: Introductionmentioning
confidence: 99%